Experimental and Numerical Investigation of the Behavior of Automotive Battery Busbars under Varying Mechanical Loads - Tobias Werling; Marvin Sprenger; Christian Ellersdorfer; Wolfgang Sinz (Energies, 2020)
Automotive high-voltage busbars are critical electrical components in electric vehicle battery systems as they connect individual battery modules and form the connection to the vehicle’s powertrain. Therefore, a vehicle crash can pose a significant risk to safety by compromising busbar insulation, leading to electrical short circuits inside the battery. In turn, these can trigger thermal chain reactions in the cell modules of the battery pack. In order to ensure a safe design in future applications of busbars, this study investigated the mechanical behavior of busbars and their insulation. Our results indicated that crashlike compressive and bending loads lead to complex stress states resulting in failure of busbar insulation. To estimate the safety of busbars in the early development process using finite element simulations, suitable material models were evaluated. Failure of the insulation was included in the simulation using an optimized generalized incremental stress state dependent model (GISSMO). It was shown that sophisticated polymer models do not significantly improve the simulation quality. Finally, on the basis of the experimental and numerical results, we outline some putative approaches for increasing the safety of high-voltage busbars in electric vehicles, such as choosing the insulating layer material according to the range of expected mechanical loads.